Evaluation of mistakes in backstroke swimming - Stibilj, J.; Košmrlj, K.; Kapus, J. (Kinesiologia Slovenica, 2020)
Purpose: We tried to determine the perceptions of experienced swimming teachers and coaches (hereinafter "experts") regarding common mistakes in backstroke swimming. Moreover, we compared their evaluation with the evaluation of participants with no professional expertise in teaching/coaching swimming (hereinafter »non-experts«). Methods: 70 participants were recruited and divided either in the experts group (E) or in the non-experts group (NE). Group E consisted of 21 swimming coaches (11 males and 10 females; ages 34 ± 11 years) with the certificate of Slovenian Swimming association and with lengthy experience (at least 10 years) in teaching and coaching swimming. 49 undergraduate students (29 males and 20 females; ages 18 ± 1 years) without any teaching or coaching experiences in swimming were assigned to Group NE. They were asked to mark 42 mistakes that most commonly occur in backstroke swimming. They evaluated these mistakes on a seven-point scale of importance for backstroke swimming performance. Results: For 27 of 42 mistakes significant differences existed in evaluations between both groups. Group NE marked them with a significantly lower score, i.e. as less important than Group E. Conclusion: In light of the results obtained by Group E, a scale of importance of mistakes for backstroke swimming was established. This scale could be used for future swimming teachers` preparation in a way to understand the principles of backstroke with greater ease. Moreover, it could help swimming teachers and coaches classify swimmers according to their backstroke technique performance.